Synthesis of new xanthone derivatives - Santos, Clementina M.M. (2005)
Xanthones are a class of heterocyclic compounds widely distributed in the plant kingdom (1). Since a long time ago, compounds with the xanthone core are of great interest for chemists, biologists and pharmacologists due to their potencial biological properties. Certain natural and synthetic derivatives have shown important anti-fungal, anti-tumour, anti-inflammatory as well as antioxidant activities (1 ,2).